On the nonemptiness of approximate cores of large games - Nizar Allouch; Myrna Wooders (Queen Mary University of London, School of Economics and Finance, 2014)
We provide a new proof of the non-emptiness of approximate cores of games with many players of a finite number of types. Earlier papers in the literature proceed by showing that, for games with many players, equal-treatment cores of their "balanced cover games", which are non-empty, can be approximated by equal-treatment e-cores of the games themselves. Our proof is novel in that we rely on a fixed point theorem.
Keywords: C71; C78; D71; 330; NTU games; Core; Approximate cores; Small group effectiveness; Coalition formation; Payoff dependent balancedness